Endothelial Extracellular Vesicles: From Keepers of Health to Messengers of Disease - Allison Mathiesen (International Journal of Molecular Sciences, 2021)
Endothelium has a rich vesicular network that allows the exchange of macromolecules between blood and parenchymal cells. This feature of endothelial cells, along with their polarized secretory machinery, makes them the second major contributor, after platelets, to the particulate secretome in circulation. Extracellular vesicles (EVs) produced by the endothelial cells mirror the remarkable molecular heterogeneity of their parent cells. Cargo molecules carried by EVs were shown to contribute to the physiological functions of endothelium and may support the plasticity and adaptation of endothelial cells in a paracrine manner. Endothelium-derived vesicles can also contribute to the pathogenesis of cardiovascular disease or can serve as prognostic or diagnostic biomarkers. Finally, endothelium-derived EVs can be used as therapeutic tools to target endothelium for drug delivery or target stromal cells via the endothelial cells. In this review we revisit the recent evidence on the heterogeneity and plasticity of endothelial cells and their EVs. We discuss the role of endothelial EVs in the maintenance of vascular homeostasis along with their contributions to endothelial adaptation and dysfunction. Finally, we evaluate the potential of endothelial EVs as disease biomarkers and their leverage as therapeutic tools.